Food consumption patterns in Colombia--a cross-sectional analysis of the DANE/DRI 1981 household survey - Sanint, Luis Roberto; Rivas Ríos, Libardo; Duque E., Myriam Cristina; Seré Rabé, Carlos (1984)
Quantitative information on Colombian consumption of different foods (among them beans) is presented by region, urban or rural sector, and income strata in terms of physical amounts, contribution to protein and calorie supply, and expenditure share. The study was based on a cross sectional survey of 9000 households undertaken by the Depto. Nacional de Planeacion and the Depto. Administrativo Nacional de Estadistica during the last trimester of 1981. Data are also included on the estimation of income, price and cross- price elasticities for various types of foods of particular relevance to CIAT research by income strata. (CIAT)